Plasma treatment of spruce wood changes its dielectric properties - Dahle, Sebastian (Les (Ljubljana), 2020)
The effects of dielectric barrier discharge (DBD) plasma treatment on the dielectric properties of Norway spruce wood (Picea abies (L.) Karst.) were investigated using dielectric analysis. Dielectric constant (i.e. permittivity) and loss coefficient were determined at various frequencies. The resulting changes on lamellae specimens of different thicknesses were compared with the change in mass and moisture content. A significant influence of the plasma was found, leading to an increase of the dielectric constant by about 2%, and a decrease of sample mass directly after the plasma treatment by approx. 14%, whereas a reduction in moisture content by only about 0.6% and a corresponding change in loss coefficient were detected. Overall, the mechanisms of the observed changes remain unclear and seem mainly uncorrelated with the hitherto known chemical changes in wood surfaces caused by similar plasma discharges.
Keywords: dielectric constant; dielektrična konstanta; les; moisture content; navadna smreka; Norway spruce; Picea abies; plasma; plazma; vlažnost; wood